In Vitro Use of Cellular Synthetic Machinery for Biosensing Applications - Lee, Kyung-Ho; Kim, Dong-Myung (Frontiers in Pharmacology, 2019)
The application of biosensors is expanding in diverse fields due to their high selectivity and sensitivity. Like other sensing devices, biosensors consist of two major parts, a recognition element and a transducer. In currently employed biosensors, the binding of the target analyte to a biological recognition element is generally transduced by electrochemical mechanisms. However, the amplifying nature of biosynthetic processes can potentially be harnessed to create fully biological sensing devices. Recent advances in the development of highly productive and cost-effective cell-free synthesis systems make it possible to use these systems as biological transducers to generate biosensing signals. This review surveys recent developments in cell-free biosensors, focusing on the newly devised mechanisms for the biological recognition of analytes to initiate the amplification processes of transcription and translation.